Catalytic anode and method for electrolytic chlorine production
By using a conductive composite metallurgy layer in the electrolytic chlorine-making system, combining the structural base composition of ruthenium, tin and titanium with the catalyst composition of cobalt oxide, the problems of high cost and poor durability of precious metals are solved, and high efficiency and low cost are achieved The catalytic anode improves the operating performance of the electrolytic chlorine production system.
Patent Information
- Application Number
- CN202410793167.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-20
- Filing Date
- 2024-06-19
- Publication Date
- 2024-12-20
AI Technical Summary
The precious metals of catalytic anode in the existing electrolytic chlorine production system are cost-effective and have poor durability, resulting in reduced efficiency loss and catalytic activity, making it difficult to meet the needs of long-term efficient operation.
Using a conductive composite metallurgical layer, it comprises a structural base composition and a catalyst composition, which consists of ruthenium, tin and titanium metal oxides scattered with voids, and the catalyst composition contains cobalt oxide crystal particles and passes through specific The process conditions and process solvent control form an efficient catalytic anode structure.
High catalytic activity, selectivity and durability are achieved, overpotential reduction, mechanical adhesion and acid corrosion resistance of the electrode are improved, operating life of the anode, and cost is reduced.
Smart Images

Figure CN119162613A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to catalytic anodes for electro-chlorination systems, which generate chlorine gas from an aqueous solution containing chloride ions by a chlorine evolution reaction. Such chlorination systems are particularly useful for industrial treatment and purification of wastewater, such as ballast water treatment systems and industrial and municipal water. They can also be used in particular for the industrial production of chlorine gas in a chlor-alkali process. Background Art
[0002] The chlorine evolution reaction ("CER") is a well-known reaction in industrial chemistry that can be used both for large-scale production of chlorine for capture and for the generation of chlorine gas for immediate use. The chlor-alkali process generates chlorine gas and sodium hydroxide by electrolysis of an aqueous sodium chloride solution; the products are recovered and put into subsequent industrial use. Chlorine gas is also an effective biocide, so electrochlorination systems are also used independently for water purification based on the in-situ generation of chlorinated water and its biocidal effect. Microbially contaminated water can be effectively treated by electrochlorination, which is deployed in various occasions such as industrial wastewater and general water sanitation. In addition, ships are increasingly carrying onboard ballast water treatment systems to treat ballast tank water before discharge. Ships sailing long distances are likely to introduce alien aquatic organisms into local ecosystems by discharging ballast water obtained at a distance. Invasive alien species can have a considerable impact on the balance of local ecosystems. Electrochlorination systems driven by generators on board provide an effective and immediate solution for treating such water before discharge.
[0003] The effective industrial application of electrolytic chlorine production systems and methods depends on electrolytic cells that can operate efficiently for a long time. In order to promote the generation of chlorine at the anode, it is common in the art to configure a catalytic coating on the surface of the anode facing the electrolyte to catalyze the chlorine evolution reaction. Such a catalytic coating usually contains a significant amount of one or more precious metals, of which iridium and ruthenium are the most commonly used, thereby significantly increasing the cost and complexity of anode manufacturing. There is still a continuous need in the art for a novel catalytic anode that can more cost-effectively meet various technical considerations related to industrial or municipal electrolytic chlorine production environments.
[0004] When selecting a catalytic coating for an electrochlorination anode, various technical considerations must be taken into account.
[0005] First, the selected catalyst must be sufficiently selective for the chlorine evolution reaction to reduce the efficiency loss caused by the competing oxygen evolution reaction that may otherwise be caused by the electrolytic separation of water in the aqueous solution at the anode. Secondly, the catalytic coating must be durable enough to withstand long-term operation and the acidification of the electrolyte that may occur with electrolytic chlorine production. Durability also requires good mechanical adhesion of the catalyst to the surface of the anode substrate. Third, the anode coating should have high conductivity to improve electrical efficiency by avoiding the need for large overpotentials to drive the electrolyzer. In fact, due to efficiency losses, a certain degree of overpotential is usually apparent in the electrolyzer; however, a lower degree of overpotential provides an important relative efficiency gain, and maintaining a lower overpotential during long-term operation provides another relevant measure of electrode durability and effective life.
[0006] The physical durability of the catalytic coating on the anode can be assessed by its performance in long-term tests and by examination of its morphology, most suitably by scanning electron microscopy. In fact, catalytic anode coatings in the art typically exhibit an outer surface morphology similar to that of a dry lake bed, with Figure 1 The appearance of finely-deposited sediments widely interrupted by characteristic "mud cracks" is shown in Figure 1. These cracks provide weak points in the catalyst layer and allow electrolyte and reactive species to penetrate downward toward the anode substrate to cause a degradation process that weakens the adhesion of the catalyst to the substrate and corrodes the exposed composition. This often results in a loss of electrical efficiency (e.g., as evidenced by an increase in overpotential) and a loss of catalytic activity and reduces the effective life of the anode, resulting in expensive replacement. Summary of the invention
[0007] The catalytic anode of the first aspect of the invention, which can be obtained by the method of the second aspect of the invention, provides a favorable balance of properties that address these technical requirements of such anodes while avoiding the need for expensive precious metals, especially iridium. In particular, the catalyst-coated anode structures defined in the first aspect of the invention exhibit high catalytic activity and selectivity for the chlorine evolution reaction, excellent durability in terms of working life and mechanical adhesion of the catalyst to the anode surface, and improved tolerance to acids formed during operation. They also have high anode conductivity so as to maintain efficient electrical operation without excessive overpotentials during long operating periods.
[0008] These advantages of the first aspect of the invention result from the deployment of an electrically conductive composite metallurgical layer of defined morphology and composition covering the electrolyte-facing surface of the anode, such composite layer comprising a specific structural base composition to support the catalyst, and a specific catalyst composition comprising essentially crystalline cobalt oxide particles. The characteristic morphology and chemical composition of such composite metallurgical layer is best achieved by a preparation method employing controlled reactants and process conditions as further defined in the second aspect of the invention.
[0009] The present invention therefore provides, in a first aspect, a catalytic anode structure for an electrolytic chlorine production system, comprising a conductive solid substrate, on the surface of the substrate facing the electrolyte, covered with a conductive composite metallurgical layer, such layer comprising:
[0010] a structural base composition coating the surface of the substrate, the structural base composition having the morphology of aggregated particles interspersed with voids and comprising metal oxide compounds of ruthenium, tin and titanium; and
[0011] a catalyst composition comprising crystalline particles of cobalt oxide distributed on the upper surface of the structural base composition and within the voids of the structural base composition; and
[0012] wherein cobalt is present in an amount of at least 12.5 atomic % of the total metallic atomic content of the composite metallurgical layer; and ruthenium and tin are present in amounts to provide the composite metallurgical layer with an overall metallic stoichiometric ratio for Ru:Sn of 1:≥1 based on the total content of ruthenium and tin in the composite metallurgical layer; and
[0013] The outer surface of the composite metallurgical layer has the morphology of a continuous coating of aggregated particles.
[0014] In the anode of the first aspect, the catalyst composition preferably further comprises one or more noble metals or oxide compounds thereof, and in particular, preferably further comprises ruthenium or an oxide thereof.
[0015] Within this specification, the term "atomic % of the total metal atomic content" with respect to a specified metal in a composition refers to the number of atoms of that metal present in the relevant composition, expressed as a percentage of the total number of atoms of the metal element present in the relevant composition, and regardless of whether such metal element is present in elemental form or in the form of a compound.
[0016] Within this specification, the term "overall metal stoichiometry" for a particular metal element refers to the stoichiometric ratio of all atoms of those metal elements present in the composite metallurgical layer (or other composition, where applicable), whether those metal elements are present in elemental form or in compound form. For example, in a structure containing 15 atomic % of ruthenium and 15 atomic % of tin in pure elemental form, the overall metal stoichiometry of Ru:Sn is 15:15 or 1:1; and in a structure containing 15 atomic % of ruthenium in the form of elemental ruthenium, 15 atomic % of elemental tin and another 15 atomic % of tin composited in the form of an oxide, the overall metal stoichiometry of Ru:Sn is 15:(15+15) or 1:2.
[0017] Within this specification, the term "morphology" is used to refer to the three-dimensional structure and appearance of the material in question. Morphology can be most effectively identified by scanning electron microscopy as described below, which provides three-dimensional imaging of the surface of a material in a manner that allows direct visual identification of its structure and appearance.
[0018] Preferably, the morphology of the structural base composition is sufficiently interspersed with voids to render the base composition porous to the catalyst composition, thereby permitting particularly extensive penetration of the catalyst composition downwardly through the thickness of the base composition when applied.
[0019] Also within this specification, the term "continuous coating" with respect to the first aspect of the invention is used to denote a coating that completely covers the underlying material. Preferably, such a continuous coating is not interrupted by significant cracks or other permeability discontinuities that would diminish its integrity. In particular, the continuous coating of the first aspect of the invention does not exhibit the extensive "mud crack" deposit morphology of conventional catalytic coatings used for electrolytic chlorine production, but rather provides a continuous surface covering or layer consisting of a three-dimensional matrix of aggregated particles as visible under scanning electron microscopy.
[0020] The present invention is based in part on the discovery that an anode structure having excellent properties for obtaining a CER reaction in electrolytic chlorine production can be advantageously obtained by coating the surface of an anode substrate with a combination of a specific structural base composition comprising tin in combination with ruthenium and titanium and an overlying CER catalyst composition substantially based on cobalt oxide. The resulting composite metallurgical layer on the anode provides the anode with a surface chemical composition and a favorable morphology to achieve excellent durability in terms of working life and mechanical adhesion of the catalyst to the anode substrate, and provides favorable catalytic activity and selectivity for the chlorine evolution reaction. The composite metallurgical layer also provides the anode with high acid corrosion resistance and high electrical conductivity to bring high electrical efficiency and long-term operating performance at low overpotential. In combination with the use of tin in the structural base composition, the use of a catalyst composition based primarily on cobalt oxide rather than a larger amount of precious metals also enables this anode performance to be achieved at a significantly lower cost than conventional catalytic anodes based on iridium and / or ruthenium as the main components.
[0021] In particular, the structural base composition essentially comprises a combination of ruthenium, tin and titanium in the form of metal oxides, wherein, as further demonstrated below, in combination with titanium, the presence of a minimum proportion of ruthenium and the co-presence of a stoichiometric amount of tin equal to or exceeding the amount of ruthenium provide a base composition capable of forming a structure having a morphology of aggregated particles interspersed with voids. Contrary to conventional thinking in the art about barrier layers, the particulate morphology of the structural base composition helps to improve the mechanical adhesion of the composite metallurgical layer on the substrate. This particulate base composition also provides an improved structural basis for the catalyst composition on the anode, the voids in the base composition allowing the catalyst composition to penetrate into the depth of the structural base layer in addition to continuously coating its outer surface, so that the highly adherent composite metallurgical layer on the surface of the anode facing the electrolyte has the above-mentioned combination of properties that are highly favorable to the chlorine evolution reaction.
[0022] This use of a defined composition comprising ruthenium, tin and titanium oxides as a structural base layer for an overlying catalytic composition is also distinct from the conventional use of one or more such oxides as the primary catalytic component in the catalyst composition, and instead relies on the specific morphology of the defined base composition to provide structural integrity to the composite metallurgical layer, thereby supporting the overlying cobalt-based catalyst composition.
[0023] In addition, the cobalt oxide crystalline particles distributed on the upper surface of the structural base composition and within the voids of the structural base composition serve as the essential catalytic species of the composite metallurgical layer and provide highly selective catalysis for the CER reaction at a cost significantly lower than that of precious metal-based catalyst compositions, such as iridium-based compositions. Although the basic cobalt oxide catalyst of the present invention can be supplemented with catalytic precious metal oxides, cobalt should be present in an amount of at least 12.5 atomic % of the total metal atomic content of the composite metallurgical layer and should represent the major catalytic species in the catalyst composition. This use of cobalt oxide as the major catalyst species is achieved by use in combination with a defined structural base composition, which combination helps to provide a highly selective, durable and efficient cobalt oxide-based catalytic anode for CER with the improved property balance described above.
[0024] Aggregated particles on the outer surface of the composite morphological layer are also necessary to provide highly effective and available surface area for catalytic activity. In particular, this particulate morphology overcomes the mass transfer limitations of conventional lakebed deposited catalyst layers to enable the catalytic anode of the first aspect of the present invention to operate the chlorine evolution reaction at a higher efficiency and contribute to the various advantages of the present invention.
[0025] The efficiency advantage of the catalytic anode of the present invention in the chlorine evolution reaction is particularly demonstrated with aqueous chloride ion solutions (such as brine) having a low salt content. The improved efficiency at low salt content provides an electrode with broad applicability to water treatment, for example, in addition to wastewater treatment and other chlorination applications, it is also suitable for municipal water applications or for treating drinking water. The improved efficiency also results in lower levels of unwanted electrolysis byproducts such as chlorate and perchlorate ions.
[0026] In a preferred form of the catalytic anode of the first aspect, the catalyst composition of the composite metallurgical layer does not contain titanium or its compounds. Such a titanium-free catalyst composition provides the resulting anode with the additional advantage of being highly suitable for current reversal cells. Current reversal has become a maintenance-friendly means for removing metal deposits such as calcium and magnesium, which otherwise may accumulate on the cathode during long electrolytic operations, especially for municipal or residential water, such as the treatment of swimming pool water, especially at low salt content. However, current reversal in the tank conventionally causes faster degradation and damage of the anode catalytic coating due to large fluctuations in pH occurring at the electrode surface, particularly within the cracked surface of the "mud-cracked" catalyst, where the electrolyte may be depleted of brine and the competitive water-splitting reaction becomes more dominant. The titanium present in the coating is easily dissolved in this environment to cause weakening of the catalytic coating on the substrate and rapid degradation of the coating and performance. The anode provided by the present invention can omit the presence of titanium in the catalyst composition due to the high efficiency of the catalyst composition and thus avoid such degradation, thereby making the anode life longer, especially in a current reversal environment.
[0027] Such a titanium-free catalyst composition also provides the resulting anode with the additional advantage of having higher resilience in high salt content processes, i.e., chlor-alkali processes. Typically, a chlor-alkali cell has a Teflon or similar membrane placed between the cathode and the anode. The caustic solution in the cell can cause holes to form in the membrane so that the caustic can reach the anode and cause titanium corrosion and consumption. The anode provided by the present invention can omit the presence of titanium in the catalyst composition due to the high efficiency of its catalyst composition and thus avoid such degradation, thereby making the anode life longer in such an environment.
[0028] Formation of the catalytic anode structure of the first aspect of the invention is best achieved by a process of sequentially adding the structural base composition and the catalyst composition under process conditions that ideally favor formation of the correct morphology of the base composition and composite metallurgical layer.
[0029] The present invention therefore provides in a second aspect a method for preparing a catalytic anode structure for an electrolytic chlorine production system, comprising the following sequential steps:
[0030] a) preparing or obtaining a conductive solid substrate;
[0031] b) applying to the electrolyte-facing surface of the substrate a conductive metallurgical composition (i) comprising providing the composition (i) with an overall metal stoichiometry of Ru ≥0.3 (Sn+Ti) ≤0.7 Compounds of ruthenium, tin and titanium in amounts;
[0032] c) optionally applying an electrically conductive metallurgical composition (ii) comprising one or more ruthenium compounds on the metallurgical layer obtained by applying the composition (i); and
[0033] (d) applying an electrically conductive metallurgical catalyst precursor composition (iii) comprising crystalline cobalt oxide particles on the metallurgical layer obtained by applying composition (i) or, with the optional application of composition (ii), by applying compositions (i) and (ii);
[0034] wherein the process solvent used to apply the metallurgical composition in steps (b) and (d) and optionally step (c) is a mixture of isopropanol and water in a ratio ranging from 80:20 to 95:5 by volume; and
[0035] Therein, the resulting structure is subsequently dried and then heat treated at a temperature of at least 450° C.
[0036] The method of the second aspect is particularly characterized in that it uses specific starting metallurgical compositions and preparation conditions to produce the anode structure of the first aspect.
[0037] First, comprising providing the starting composition (i) with an overall metal stoichiometry of Ru ≥0.3 (Sn+Ti) ≤0.7 The use of an electrically conductive metallurgical composition (i) of compounds of ruthenium, tin and titanium in amounts of 100% to 100% yields, under the process conditions of the second aspect, a structural base layer of a composite metallurgical layer of the anode that provides a favorable foundation for the overlying catalyst composition. The defined overall metal stoichiometry of the starting composition (i) brings about in particular the desired morphology of the resulting structural base layer, which is a layer having the morphology of aggregated particles interspersed with voids. Such formation of the desired base composition morphology is further facilitated by the use of a defined process solvent and, in some preferred embodiments, by heating the anode substrate to a temperature in the range of 50-200° C. during the application step (b).
[0038] During the application step (b), the use of a process solvent that is volatile under these conditions further enables the formation of voids in the structural base layer into which the catalyst composition (iii) subsequently applied in step (d) (and the optional composition (ii) applied in step (c)) can advantageously penetrate. Such a solvent also results in the concomitant loss of a certain proportion of the more volatile metal salts contained within the defined metallurgical content of the starting composition (i), so that a metallurgical layer having an overall metal stoichiometry different from that of the starting composition (i) is formed with respect to ruthenium, tin and titanium. The use of a defined composition (i) and defined process conditions is believed to advantageously accommodate this concomitant loss of metal salt volatility and results in the formation of an applied metallurgical layer having a desired composition and morphology.
[0039] The specified process solvents and subsequent heat treatment of the resulting structure during application step (d) (and, when present, optional application step (c)) also contribute to the favorable morphology and composition of the resulting composite metallurgical layer on the anode of the present invention.
[0040] In a preferred embodiment, applying the metallurgical compositions (i) and (iii) (and, where present, composition (ii)) to a substrate which is heated to a specified temperature range of 50-200°C during the application process (preferably heated to this temperature range throughout the application process) has been found to further enhance the formation of the desired composite metallurgical layer on the anode.
[0041] Drying of the resulting structure at the same temperature range of 50-200°C has also been found to further enhance the formation of the desired composite metallurgical layer, particularly by facilitating the formation of the desired morphology of a continuous layer uninterrupted by mud cracks or other significant penetrating discontinuities.
[0042] It has been found that a final heat treatment of the resulting structure at a temperature of at least 450°C is essential for enhancing the formation of the desired composite metallurgical layer, in particular by facilitating improved mechanical adhesion of the composite metallurgical layer to the anode substrate, and by facilitating a high selectivity of the chlorine evolution reaction relative to the oxygen evolution reaction from water decomposition. In this regard, a second aspect of the invention preferably is a final heat treatment in the range of 450 to 600°C, in particular an optimal final heat treatment at 500°C, where higher selectivity and mechanical adhesion to the chlorine evolution reaction are observed.
[0043] The second aspect of the present invention also requires that the metallurgical composition is applied using a specified process solvent in steps (b) and (d) and optional step (c), which is a mixture of isopropanol and water in a ratio range of 80:20 to 95:5 by volume, preferably in a ratio range of 82.5:17.5 to 87.5:12.5 by volume. Most preferably, the process solvent is a mixture of isopropanol and water in a volume ratio of 85:15. For the solubility of the starting compound used in the method of the second aspect, it has been found that this composition of the process solvent exhibits advantages over similar alcoholic solvents. In addition, it has been found that this composition of the process solvent advantageously controls the surface morphology of the layer formed by applying the metallurgical composition before and after the final heat treatment step, and is particularly helpful for the aggregated particle morphology of the structural base composition without cracks that weaken integrity. This ability to control the morphology of the layer is particularly attributed to the selection of the alcohol in the process solvent and the ratio of alcohol to water, and is best controlled at a volume ratio of 85:15 (isopropanol: water).
[0044] Further aspects of the invention are also described herein and include:
[0045] An electrolytic chlorine production system comprising the electrolytic anode structure of the first aspect or the electrolytic anode structure obtainable by the method of the second aspect; and
[0046] An electrolytic method for catalyzing the evolution of chlorine gas from an aqueous solution containing chloride ions, comprising passing an electric current through the solution in an electrolytic cell comprising the electrolytic anode structure of the first aspect or the electrolytic anode structure obtainable by the method of the second aspect, wherein chlorine gas is evolved from the aqueous solution at the anode.
[0047] In a preferred aspect of the electrolysis process, the chlorine gas evolved by the process is used as a biocide to disinfect water, more particularly for disinfecting ballast water or industrial wastewater, or municipal or domestic water, such as recreational water in swimming pools and domestic drinking water. In an alternative preferred aspect, the process is a chlor-alkali process for generating and recovering chlorine gas.
[0048] The present invention will now be described in more detail as follows: BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In this application, the following drawings are included:
[0050] Figure 1 : Lake bed morphology of conventional catalyst layer with extensive “mud cracks”;
[0051] Figure 2 : Aggregate particle morphology of a preferred embodiment of the present invention;
[0052] Figure 3TOF-SIMS (Time-Of-Flight Secondary Ion Mass Spectrometry) concentration-depth profile of a preferred embodiment of the present invention (Example 1);
[0053] Figure 4 :TOF-SIMS (Time of Flight Secondary Ion Mass Spectrometry) concentration-depth profile of a preferred embodiment of the present invention (Example 2);
[0054] Figure 5 : Anode Life Test – Effect of the ruthenium stoichiometry in the composition (i) of the method on the durability of the structural base composition;
[0055] Figure 6 : Anode life test – Effect of structural base metal composition;
[0056] Figure 7 : Scanning electron microscope (SEM) examination of the comparative base composition after application to the substrate,
[0057] Figure 7 (a): Ru-Sn based base layer on titanium mesh substrate (comparison);
[0058] Figure 7 (b): Ti-Ru-Sn base layer on a titanium mesh substrate (the present invention); and
[0059] Figure 7 (c): from Figure 7 (b) High magnification image of the base layer;
[0060] Figure 8 : Improved anode life due to the presence of the base structural layer;
[0061] Fig. 9 : Further advantages resulting from the application of the optional composition (ii) on the anode by the method according to the invention;
[0062] Fig.10 : an improvement in anode life resulting from the preferred inclusion of tin and antimony in defined stoichiometric amounts in composition (iii) of the process (ATO = total amount of antimony and tin); and
[0063] Fig.11 : CER efficiency improvement and lifetime improvement brought about by including tin and antimony in a defined stoichiometry in the composition (iii) of the method (ATO = total amount of antimony and tin)
[0064] Fig.11(a): Chlorine evolution efficiency (CER) of the electrode of the present invention corresponding to various stoichiometric ratios of Sn and Sb in the preferred catalyst precursor composition (iii);
[0065] Fig.11 (b): Lifetime improvement resulting from the inclusion of tin and antimony in defined stoichiometric amounts in the composition (iii) of the process. DETAILED DESCRIPTION
[0066] First Aspect of the Invention (Catalytic Anode)
[0067] The catalytic anode structure of the first aspect comprises a conductive solid substrate covered on its surface facing the electrolyte with a conductive composite metallurgical layer comprising:
[0068] a structural base composition coating the surface of the substrate, the structural base composition having the morphology of aggregated particles interspersed with voids and comprising metal oxide compounds of ruthenium, tin and titanium; and
[0069] a catalyst composition comprising crystalline particles of cobalt oxide distributed on the upper surface of the structural base composition and within the voids of the structural base composition; and
[0070] wherein cobalt is present in an amount of at least 12.5 atomic % of the total metal atomic content of the composite metallurgical layer; and ruthenium and tin are present in amounts to provide the composite metallurgical layer with an overall metal stoichiometric ratio of Ru:Sn of 1:≥1 based on the total content of ruthenium and tin in the composite metallurgical layer; and
[0071] The outer surface of the composite metallurgical layer has the morphology of a continuous coating of aggregated particles.
[0072] The anode structure of the first aspect of the present invention is obtainable by the method of the second aspect of the present invention, and is preferably obtained by the method of the second aspect of the present invention.
[0073] The anode structure of the first aspect is characterized in that the outer surface of the composite metallurgical layer has the morphology of a continuous coating of aggregated particles. This broadest scope of the first aspect does not exclude the presence of occasional cracks or other surface discontinuities or fault lines, where these defects do not exceed the depth of penetration of the catalytic composition into the metallurgical layer or expose the underlying substrate to electrolyte corrosion. However, preferably, the composite metallurgical layer of the anode structure of the first aspect has the outer surface morphology of a continuous uncracked coating of aggregated particles.
[0074] The aggregated particulate morphology of the outer surface of the composite metallurgical layer contrasts with the extensively cracked, deposit-like surface morphology of conventional catalytic anodes and can be best visualized by examination under scanning electron microscopy as shown in the accompanying figures. In each case, the JSM-IT500 InTouchScope TM Scanning electron microscopy instrument, Scanning electron micrographs were obtained using the settings specified in the legends to the relevant figures.
[0075] exist Figure 1 Scanning electron microscopy of the external surface morphology of a conventional catalytic anode used for electrolytic chlorine production shows a characteristic "mud crack" appearance, with extensive deep cracks radiating through a sediment-like surface coating. Such morphology renders the catalytic surface susceptible to chemical attack and weakens its structural integrity, reducing its life and usefulness.
[0076] On the contrary, Figure 2 , scanning electron microscopy shows the characteristic surface of a preferred catalytic anode of the first aspect, with a continuous uncracked surface layer and aggregated particulate morphology visible at the magnification shown.
[0077] An essential element of the anode structure of the first aspect is the presence of cobalt oxide in an amount of at least 12.5 atomic % of the total metal atomic content of the composite metallurgical layer. The anode of the present invention provides a means for configuring a high content of cobalt oxide-based catalyst in the anode in a form that is highly selective for electrolytic chlorine production, which provides excellent durability in terms of working life and mechanical adhesion of the catalyst to the anode substrate, high acid corrosion resistance and high conductivity to bring high electrical efficiency and operating performance at low overpotentials. The use of a catalyst composition based on cobalt oxide as the main catalytic metal rather than a precious metal also enables this anode performance to be achieved at a significantly lower cost than conventional precious metal-based catalysts, such as iridium-based catalytic anodes.
[0078] Preferably, in the anode structure of the first aspect, cobalt oxide is present in the highest amount practicable to maximize its catalytic effect while achieving the other advantages of the invention. Therefore, preferably, cobalt is present in an amount of at least 15 atomic % of the total metal atomic content of the composite metallurgical layer, more preferably in an amount of at least 20 atomic % of the total metal atomic content of the composite metallurgical layer. Even more preferably, cobalt is present in an amount of at least 30 atomic % of the total metal atomic content of the composite metallurgical layer, most preferably in an amount of at least 40 atomic % of the total metal atomic content of the composite metallurgical layer. Ideally, cobalt is present in an amount in the range of 50 to 80 atomic % of the total metal atomic content of the composite metallurgical layer, preferably in the range of 60 to 75 atomic % of the total metal atomic content of the composite metallurgical layer. Such a cobalt content is advantageously achieved by preparing an anode structure according to the method of the second aspect of the invention.
[0079] It is also essential to the present invention that ruthenium and tin are present in an amount that provides the composite metallurgical layer with an overall metal stoichiometric ratio of Ru:Sn of 1:≥1 based on the total content of ruthenium and tin in the composite metallurgical layer. An important discovery of the present invention is the advantageous use of tin in an overall stoichiometric amount at least equal to the amount of ruthenium, which enables a significant reduction in the total ruthenium content of the electrode coating, while also contributing to the advantageous combination of properties exhibited by the composite metallurgical layer of the present invention. In particular, the presence of a defined amount of tin contributes to the mechanical integrity of the layer and its electrical conductivity.
[0080] The overall metal stoichiometric ratio of Ru:Sn based on the total content of ruthenium and tin in the composite metallurgical layer is preferably 1:≥1.5, more preferably 1:≥2. Even more preferably, the overall metal stoichiometric ratio of Ru:Sn based on the total content of ruthenium and tin in the composite metallurgical layer is 1:≥3, most preferably 1:≥5. The optimal value of this ratio in the present invention is in the range of 1:8 to 1:20, for example in the range of 1:8 to 1:15.
[0081] The above preferred ranges of the cobalt content in the composite metallurgical layer and the overall metal stoichiometric ratio of Ru:Sn can be combined to achieve the best effect in the anode structure of the first aspect of the present invention. In particular, more preferred embodiments of the first aspect include:
[0082] 1) The anode structure of the first aspect, wherein cobalt is present in an amount of at least 15 atomic % of the total metal atomic content of the composite metallurgical layer, and the overall metal stoichiometric ratio of Ru:Sn based on the total content of ruthenium and tin in the composite metallurgical layer is 1:≥1.5; more preferably
[0083] 2) The anode structure of the first aspect, wherein cobalt is present in an amount of at least 20 atomic % of the total metal atomic content of the composite metallurgical layer, and the overall metal stoichiometric ratio of Ru:Sn based on the total content of ruthenium and tin in the composite metallurgical layer is 1:≥1.5, or more advantageously 1:≥2; more preferably
[0084] 3) The anode structure of the first aspect, wherein cobalt is present in an amount of at least 30 atomic % of the total metal atomic content of the composite metallurgical layer, and the overall metal stoichiometric ratio of Ru:Sn based on the total content of ruthenium and tin in the composite metallurgical layer is 1:≥1.5, or more advantageously 1:≥2, most advantageously 1:≥3; more preferably
[0085] 4) The anode structure of the first aspect, wherein cobalt is present in an amount of at least 40 atomic % of the total metal atomic content of the composite metallurgical layer, and the overall metal stoichiometric ratio of Ru:Sn based on the total content of ruthenium and tin in the composite metallurgical layer is 1:≥1.5, or more advantageously 1:≥2, most advantageously 1:≥3, ideally 1:≥5; most preferably
[0086] 5) The anode structure of the first aspect, wherein cobalt is present in an amount of 50 to 80 atomic % of the total metal atomic content of the composite metallurgical layer, and the overall metal stoichiometric ratio of Ru:Sn based on the total content of ruthenium and tin in the composite metallurgical layer is 1:≥1.5, or more advantageously 1:≥2, most advantageously 1:≥3, and ideally 1:≥5.
[0087] A particularly preferred anode structure of the first aspect is one in which cobalt is present in an amount of at least 40 atomic % of the total metal atomic content of the composite metallurgical layer; and ruthenium and tin are present in amounts to provide the composite metallurgical layer with an overall metal stoichiometric ratio of Ru:Sn of 1:≥5 based on the total content of ruthenium and tin in the composite metallurgical layer.
[0088] The optimal anode structure of the first aspect is that cobalt is present in an amount of 50 to 80 atomic % of the total metal atomic content of the composite metallurgical layer; and ruthenium and tin are present in amounts to provide the composite metallurgical layer with an overall metal stoichiometric ratio of Ru:Sn of 1:≥5, preferably in the range of 1:8 to 1:15, based on the total content of ruthenium and tin in the composite metallurgical layer.
[0089] The individual metal contents and overall metal stoichiometry of the composite metallurgical layer may be measured by known techniques using ICP-MS (Inductively Coupled Plasma Mass Spectrometry) to determine the compositional characteristics of the present invention.
[0090] In the anode structure of the first aspect, it is preferred that the cobalt oxide crystalline particles in the catalyst composition are substantially composed of particles having the chemical formula Co 3 O 4 In one such embodiment, the cobalt oxide crystalline particles may be composed of a crystalline cobalt oxide having the formula Co 3 O 4 The presence of this crystalline form of cobalt oxide can be confirmed by X-ray diffraction or other conventional crystallographic techniques. 3 O 4 The size of the crystalline particles can be determined by directly measuring their diameter in a transmission electron microscopy image, and is preferably 1 nm to 20 nm in diameter, more preferably 1 nm to 10 nm, and most preferably 3 to 7 nm in diameter.
[0091] In the anode of the first aspect, the catalyst composition preferably further comprises one or more noble metals or oxide compounds thereof, in particular ruthenium or an oxide thereof. In keeping with the objectives of the present invention, the amount of any noble metal included should be sufficiently small so that the cobalt content of the composite metallurgical layer does not drop below the level specified in the present invention, and the amount of the noble metal should preferably not exceed 10 atomic %, more preferably not more than 5 atomic % of the total metal atomic content of the composite metallurgical layer.
[0092] In a more preferred embodiment, the cobalt oxide crystalline particles in the catalyst composition consist essentially of the chemical formula Co 3 O 4 The catalyst composition is a crystalline cobalt oxide having a composition of 50% by weight and further essentially comprising ruthenium or its oxide to a ruthenium content of up to 5 atomic % based on the total metal atomic content of the crystalline particles, at least some of which is preferably present in the form of surface decoration on the crystalline particles. In this latter embodiment of the anode, the crystalline cobalt oxide particles in the catalyst composition may further contain crystalline regions in which, in addition to the surface decoration, ruthenium is incorporated into the crystal lattice of the cobalt oxide, or has formed a mixed metal oxide with cobalt, or both.
[0093] The limited amount of ruthenium combined with the cobalt oxide crystalline particles in the catalyst composition provided in these embodiments provides the property of the composite metallurgical layer on the anode to be further improved, most especially the selectivity of the catalyst to the chlorine evolution reaction and the advantage of improving the durability (particularly in terms of operating life) of the anode. At least in the case of being incorporated into the lattice of cobalt oxide, ruthenium may exist in the form of an oxide compound or in the form of a metallic element. The ruthenium combined with the cobalt oxide catalyst in these embodiments may exist in an overall non-stoichiometric ratio, close to a mixture of elemental ruthenium and oxide-bound ruthenium.
[0094] However, for the ruthenium content in the crystalline particles of the catalyst composition, it has been found that exceeding the upper limit of 5% leads to a reduction in the efficiency of the chlorine evolution reaction, especially for water treatment applications, as evidenced by a reduction in low salt efficiency. Therefore, the ruthenium content associated with the cobalt oxide catalytic particles should be limited to a specified level, and further increases in the ruthenium content are not beneficial to any expectations of further improvements.
[0095] In all of the above embodiments of the anode of the first aspect, the composite metallurgical layer comprises a catalyst composition comprising crystalline particles of cobalt oxide, which are distributed on the upper surface of the structural base composition and within the voids of the structural base composition. Preferably, the catalyst composition consists essentially of crystalline particles of cobalt oxide distributed in a matrix of other metal oxides, especially a crystalline matrix of other metal oxides, especially wherein these other metal oxides do not contain a significant amount or any amount of precious metal oxides other than those provided herein with respect to the present invention, such as palladium or iridium.
[0096] In particular, it is preferred in all embodiments of the anode that the catalyst composition comprises crystalline particles of cobalt oxide in a crystalline matrix of antimony and tin oxides, and preferably consists essentially of crystalline particles of cobalt oxide in a crystalline matrix of antimony and tin oxides; such catalyst composition is present on the upper surface of the structural base composition and in the voids of the structural base composition. In such an embodiment of the anode, it is preferred that the overall metal stoichiometric ratio of the total amount of cobalt: antimony and tin in the composite metallurgical layer is in the range of 2:1 to 9:1. More preferably, the overall metal stoichiometric ratio of the total amount of cobalt: antimony and tin in the composite metallurgical layer is in the range of 2.5:1 to 6:1, most preferably in the range of 3:1 to 5:1. Optimally, the overall metal stoichiometric ratio of the total amount of cobalt: antimony and tin in the composite metallurgical layer is in the range of 3:1 to 4:1. It has been surprisingly found that the overall metal stoichiometric ratio of the total amount of cobalt: antimony and tin in the composite metallurgical layer provides favorable performance. By keeping this ratio within the above-mentioned general range, the durability of the catalytic anode is improved as evidenced by the increase in its effective working life. This increase in lifetime provides a very advantageous property for the anode of the first aspect.
[0097] In the above-described anode embodiments, it is more preferred that the antimony and tin compounds serving as the matrix in the catalyst composition are also present in an amount to provide the composite metallurgical layer with an overall metal stoichiometric ratio of antimony:tin in the range of 1:5 to 1:200, preferably in the range of 1:5 to 1:100.
[0098] In this regard, it has been further surprisingly found that the overall metal stoichiometry of antimony:tin in the composite metallurgical layer provides a further contribution to achieving optimal anode performance. Maintaining this overall metal stoichiometry within the above range provides further improved operating life for the anode and also improves the CER efficiency of the electrolytic cell as evidenced by the Faraday efficiency.
[0099] In this regard it is preferred that the antimony and tin compounds are present in an amount to provide the composite metallurgical layer with a preferred overall metal stoichiometric ratio of antimony:tin in the range of 1:25 to 1:100, most preferably in the range of 1:30 to 1:85. This ratio may best be in the range of 1:50 to 1:85, with excellent embodiments being 1:75 and 1:84.
[0100] In each of the above embodiments of the anode structure, it is preferred that the composite metallurgical layer further comprises at least one palladium compound in an amount providing a total palladium content of up to 7 atomic % of the total metal atomic content of the composite metallurgical layer. It is preferred that a limited amount of palladium is introduced into the composite layer by including one or more palladium-based compounds in the catalyst composition or by subsequent doping. As demonstrated by the increase in low-salt efficiency, palladium provides a further improvement in the efficiency of the chlorine evolution reaction, particularly for water treatment applications.
[0101] However, the palladium content in the catalyst composition exceeding the upper limit of 7 atomic % does not bring further improvement in the efficiency of the chlorine evolution reaction, especially for water treatment applications, as evidenced by the lack of further improvement in low salt efficiency. Therefore, the palladium content combined with the cobalt oxide catalytic particles should be limited to a specified level to avoid unnecessary cost and complexity. Preferably, the total palladium content is at most 5 atomic %, more preferably at most 3 % of the total metal atomic content of the composite metallurgical layer; and optimally, the total palladium content is at most 1.5 % of the total metal atomic content of the composite metallurgical layer.
[0102] The anode of all embodiments of the first aspect is essentially composed of a conductive solid substrate, which is known in the art. Such a substrate is preferably essentially composed of a valve metal such as titanium, zirconium, niobium and tantalum (and alloys / mixtures containing these metals), preferably titanium, and most preferably essentially composed of titanium. A mixture of valve metals may be present in the substrate. It may be additionally observed or produced as an artificial product under the conditions of anode manufacturing and use that the oxide of the valve metal is essentially present in the substrate, particularly at the surface of the substrate or at its interface with the composite metallurgical layer, and the substrate of the present invention does not exclude their presence, as long as they do not form the main constituent component of the substrate.
[0103] Anode substrates can be produced by conventional means in the art and can be purchased or manufactured to order and formed into any shape suitable for final use as an anode in an electrochemical cell or system. In particular, the substrate can be formed into meshes, plates, and more complex three-dimensional shapes such as cylinders. Depending on their design and arrangement, the substrate can be coated with a composite metallurgical layer on one or more sides.
[0104] In the anode of all embodiments of the first aspect, the distribution of the cobalt oxide-based catalyst composition extends down into the depth of the composite metallurgical layer as it penetrates and occupies the interstices of the structural base composition. The distribution of the metal elements in the thickness of the structure of the composite metallurgical layer according to the present invention can be visualized by imaging using a transmission electron microscope (TEM) according to the mapping technique TEM-EDS (transmission electron microscopy and energy dispersive X-ray spectroscopy).
[0105] Using the TEM-EDS technique, the distribution of various basic constituent metals can be directly imaged and their distribution within the thickness of the composite metallurgical layer can be observed to confirm the presence of the anode structure of the present invention, especially when compared with the overall image obtained by HAADF (High-Angle Annular Dark Field transmission electron microscopy). Using the TEM-EDS mapping technique, each metal element within the composite metallurgical layer can be visualized individually. In particular, the cobalt of the cobalt oxide particles is easily observed in a dense concentration (coating) on the outer surface of the composite layer, but due to penetration into the base composition according to the present invention, the cobalt is also visible in the entire depth of the composite layer at a lower density. Ruthenium, which is present in the catalyst composition at a lower content than the structural base composition, therefore appears in the surface area of the higher cobalt catalyst density on TEM-EDS, and appears in the area of the base composition at a higher density; while the titanium of the base composition is mostly confined to this area of the composite layer and rarely migrates to the concentration of the catalyst composition on the surface. Tin is distributed throughout the layer, both in the base composition and in the antimony-tin matrix of the catalyst composition.
[0106] The distribution and concentration of metal elements throughout the composite metallurgical layer can also be quantitatively measured using TOF-SIMS (Time-Of-Flight Secondary Ion Mass Spectrometry). This technique is capable of mapping metal concentrations down through the depth of the composite metallurgical layer and can also confirm the presence of the structures of the present invention, such as Figure 3 and 4 , which maps the concentrations of titanium, ruthenium, tin and cobalt through the depth of the composite metallurgical layer of the corresponding samples of the present invention.
[0107] In more detail, by cutting 1 cm of the coated electrode for SIMS loading 2 The samples were prepared for TOF-SIMS, and the TOF-SIMS analysis was performed using an ion source: Cs+ ions, current: 3keV, 20nA, and a sputtering area: 150μm×150μm to detect ions as Cs+ adsorbed secondary ions (Cs+-metal) to minimize any matrix effects. Depth measurements were determined after sputtering for depth calculations. A quantitative calculation method was used, whereby RSF (relative sensitivity factor) was calculated by the following formula:
[0108] Intensity / Concentration = RSF
[0109] The concentration of each metal element was obtained by ICP-MS and used together with the intensity of each element (at depth) from TOF-SIMS to calculate the RSF to deduce the depth distribution of each metal.
[0110] In the anode of the first aspect, it is preferred that the cobalt of the catalyst composition is non-uniformly distributed throughout the thickness of the composite metallurgical layer, with the concentration of cobalt oxide being higher in the composite metallurgical layer adjacent its outer surface than adjacent the substrate surface, as determined, for example, by the above-described techniques. Such a preferred embodiment is shown in Figure 3 and 4 , which shows the characteristic inhomogeneous distribution of cobalt in the depth of the composite metallurgical layer.
[0111] In a further enhanced embodiment of the anode of the first aspect, the composite metallurgical layer further comprises ruthenium oxide distributed throughout or substantially distributed throughout the base structure composition and the catalyst composition. In particular, it is preferred that the ruthenium oxide is distributed in a matrix of the catalyst composition, which is more preferably distributed in the preferred catalyst matrix of antimony and tin oxides described above. The inclusion of ruthenium oxide throughout or substantially distributed in the composite metallurgical layer further improves the conductivity of the layer and improves the low-salt efficiency of the anode, and also improves the long-term durability of the anode structure.
[0112] Ruthenium oxide can be most advantageously included in the composite metallurgical layer by being applied as an intermediate layer (or "interlayer") between the application of the structural base composition and the catalyst composition during the method of the second aspect, with subsequent heat treatment of the resulting structure causing the ruthenium oxide interlayer to migrate throughout the composite layer to enhance the conductive path through the composite layer and bring about the other advantages identified above.
[0113] The structural base composition of all embodiments of the anode of the first aspect comprises, preferably consists essentially of, a metal oxide compound of ruthenium, tin and titanium to achieve a desired stoichiometric ratio of Ru: Sn. The combination of these three metals is important for obtaining the correct morphology of the structural base composition in situ on the anode surface. Other metal oxides or other compounds may be present in addition as long as they do not adversely affect the base composition morphology, but most preferably, the structural base composition consists of a metal oxide compound of ruthenium, tin and titanium.
[0114] In particular, the specific combination of ruthenium, tin and titanium provides a base structure composition that exhibits a desired particulate base morphology and is therefore also resistant to significant cracking and preferably crack-free, to provide a resilient base structure onto which the catalyst composition can be applied. In contrast, conventional coating compositions based on ruthenium and tin, for example, typically exhibit a sediment-like "mud crack" surface and do not provide the same resilient base for subsequent compositions.
[0115] In addition, the specific combination of ruthenium, tin and titanium in the structural base composition provides improved durability for the anode of the first aspect of the invention compared to similar base compositions containing only ruthenium and titanium or only ruthenium and tin. In this regard, the combination of both tin and titanium with ruthenium provides improved anode life and improved mechanical adhesion for the anode of the invention and further contributes to the advantages of the invention.
[0116] The ruthenium, tin and titanium oxides of the structural base composition also contribute substantially to the overall stoichiometry of these metals in the composite metallurgical layer of the anode of the first aspect, and therefore the respective contents of ruthenium, tin and titanium within the structural base composition should be adjusted according to the skills in the art to achieve the desired overall stoichiometry of the composite metallurgical layer.
[0117] However, in practice, when the process conditions of the second aspect of the present invention are adopted, the metal stoichiometry Ru ≥0.3 (Sn+Ti) ≤0.7 The application of the starting composition of the structural base will achieve the appropriate overall stoichiometry of these metals within the composite metallurgical layer, and for the method of the second aspect, it is important that ruthenium is present at a stoichiometric level of at least 0.3 in the starting base composition to obtain the anode and advantages of the present invention. However, taking into account any additional contribution of tin or ruthenium from certain embodiments of the catalyst composition, for example, a skilled person can vary this starting base composition to obtain a particularly desired overall metal stoichiometry.
[0118] The above-described embodiments of the first aspect of the invention may further comprise, in addition to the above-described features, one or more additional constituent elements for enhancing specific properties of the anode, provided that the overall advantages of the invention are still obtained. For example, in the anode structure of any of the foregoing embodiments, the base structure composition or the catalyst composition or both further comprises a noble catalytic metal (if palladium is present, in addition to any palladium), preferably iridium, in the form of its oxide or other catalytically active species, in an amount that provides a total additional noble metal content, preferably iridium content, of up to 15 atomic %, preferably up to 10 atomic %, and more preferably up to 7 atomic % of the total metal atomic content of the composite metallurgical layer. The optional presence of such small amounts of noble metal, especially iridium, may be advantageous from the perspective of further enhancing the catalytic performance of the anode, but for the purposes of the present invention, should be limited to minimize the use of expensive noble metals and rely primarily on cobalt oxide for catalytic activity. Therefore, such amounts of noble metals are much lower than the amounts typically used when the catalyst composition is based on such metals.
[0119] Alternatively or additionally, the anode composite metallurgical layer of all embodiments may further include at least one copper compound, the amount of which is the composite metallurgical layer providing the composite metallurgical layer with a total metal atomic content of up to 10 atoms, preferably up to 2 atoms of the total copper content; or at least one aluminum compound, the amount of which is the total metal atomic content of the composite metallurgical layer provided by the layer is up to 30 atoms, preferably up to 20 atoms of the total aluminum content; at least one nickel compound, the amount of which is the total metal atomic content of the composite metallurgical layer provided by the layer is up to 15 atoms, preferably up to 10 atoms of the total nickel content; or more than one of these. For example, as measured by low salt efficiency, the additional presence of copper, aluminum or nickel in the composite metallurgical layer provides further improved catalyst selectivity for chlorine evolution reaction. Therefore, although copper and / or aluminum and / or nickel may be distributed throughout the composite layer, it is preferred that copper and / or aluminum and / or nickel are introduced via the catalyst composition and are present in the catalyst composition, for example in the form of one or more oxide compounds.
[0120] The second aspect of the present invention (preparation method)
[0121] A second aspect provides a method for preparing a catalytic anode structure for an electrolytic chlorine production system, comprising the following sequential steps:
[0122] a) preparing or obtaining a conductive solid substrate;
[0123] b) applying to the electrolyte-facing surface of the substrate a conductive metallurgical composition (i) comprising providing the composition (i) with an overall metal stoichiometry of Ru ≥0.3 (Sn+Ti) ≤0.7 Compounds of ruthenium, tin and titanium in amounts
[0124] c) optionally applying an electrically conductive metallurgical composition (ii) comprising one or more ruthenium compounds on the metallurgical layer obtained by applying the composition (i); and
[0125] (d) applying an electrically conductive metallurgical catalyst precursor composition (iii) comprising crystalline cobalt oxide particles on the metallurgical layer obtained by applying composition (i) or, with the optional application of composition (ii), by applying compositions (i) and (ii);
[0126] wherein the process solvent used to apply the metallurgical composition in steps (b) and (d) and optionally step (c) is a mixture of isopropanol and water in a ratio ranging from 80:20 to 95:5 by volume; and
[0127] Therein, the resulting structure is subsequently dried and then heat treated at a temperature of at least 450° C.
[0128] The method of the second aspect of the invention results in a catalytic anode structure as defined under the first aspect of the invention and is the preferred method for preparing the anode of the first aspect.
[0129] In the method of the second aspect, defined temperature conditions and process solvents are important to obtain the desired catalytic anode structure.
[0130] In the method, the resulting structure is heat treated at a temperature of at least 450° C., preferably at a temperature in the range of 450 to 600° C., such as 450 to 550° C. More preferably, the resulting structure is heat treated at a temperature in the range of 475 to 525° C., most preferably at 500° C.
[0131] The method of the present invention also requires applying the metallurgical composition in steps (b) and (d) and optional step (c) using a specified process solvent, which is a mixture of isopropanol and water in a ratio range of 80:20 to 95:5 by volume, preferably in a ratio range of 82.5:17.5 to 87.5:12.5 by volume. Most preferably, the process solvent is a mixture of isopropanol and water in a volume ratio of 85:15.
[0132] With respect to the solubility of the starting compounds used in the method of the second aspect, it has been found that this composition of the process solvent exhibits advantages over similar alcoholic solvents. In addition, it has been found that this composition of the process solvent advantageously controls the surface morphology of the layer formed by applying the metallurgical composition before and after the final heat treatment step, and is particularly helpful in obtaining an aggregated particulate morphology of the structural base composition, more preferably without cracks that weaken integrity. This ability to control the layer morphology is particularly attributed to the choice of alcohol in the process solvent and the ratio of alcohol to water, and is best controlled at a volume ratio of 85:15 (isopropanol:water).
[0133] Preferably, in the process of the present invention, the anodic substrate (a) is heated to a temperature in the range of 55-200° C. during steps (b) and (d) and, if present, step (c), and the resulting structure is thereafter dried at a temperature in the same range. Preferably, the heating of the anodic substrate to this temperature range is performed throughout steps (b) and (d) and, if present, step (c), and the resulting structure is thereafter dried at a temperature in the same range. Optimally, the substrate (a) is heated to a temperature of 100° C. throughout steps (b) and (d) and, if present, step (c), and the resulting structure is thereafter dried at this temperature.
[0134] The use of a defined process solvent that is volatile under the conditions, and, if present, heat treatment of the substrate during the application step (b) of the process, enables the formation of voids in the structural base layer, into which the catalyst composition (iii) applied subsequently in step (d) (and the optional composition (ii) applied in step (c)) can advantageously penetrate. The use of a defined process solvent during the application step (d) (and, if present, the optional application step (c)), and the specified heating of the substrate, if present, and the subsequent drying and heat treatment of the resulting structure, also contribute to the formation of a favorable morphology and composition of the resulting composite metallurgical layer on the anode of the present invention.
[0135] In particular, application of the metallurgical compositions (i) and (iii) (and, if present, composition (ii)) to a substrate preferably heated in accordance with the second aspect of the invention has been found to enhance the formation of the desired composite metallurgical layer on the anode. It has also been found, importantly, that drying of the resulting structure at the same temperature range enhances the formation of the desired composite metallurgical layer, particularly by facilitating the formation of the desired morphology of a continuous layer, especially a continuous layer that is not interrupted by mud cracks or other significant permeability discontinuities.
[0136] It has been found that the necessary final heat treatment of the resulting structure at a temperature of at least 450°C enhances the formation of the desired composite metallurgical layer, in particular by facilitating improved mechanical adhesion of the composite metallurgical layer to the anode substrate, and by facilitating a high selectivity of the chlorine evolution reaction relative to the oxygen evolution reaction from water decomposition. In this regard, a second aspect of the invention preferably is a final heat treatment in the range of 450 to 550°C, in particular an optimal final heat treatment at 500°C, where a higher selectivity for the chlorine evolution reaction and mechanical adhesion is observed.
[0137] The use of the temperature conditions and process solvents defined above in the method of the second aspect, combined with the defined metallurgical contents of the starting compositions (i) and (iii) (and preferably, composition (ii) if present), results in the formation of a composite metallurgical layer of the desired composition and morphology on the anode substrate, which is suitable for use as the anode of the first aspect.
[0138] In the method of the second aspect, the composition (i) applied in step (b) comprises providing the composition (i) with an overall metal stoichiometry of Ru ≥0.3 (Sn+Ti) ≤0.7The composition (i) is the starting composition of the structural base composition of the composite metallurgical layer, and it is important in the method of the second aspect of the invention that the ruthenium content of the composition (i) is at a level of 0.3 or more (corresponding to 30 atomic %) stoichiometrically relative to the tin and titanium present in the composition in order to achieve the desired basic structure. It has been found that when the ruthenium in the starting composition (i) is at or above this level, the durability of the resulting structural base composition is greatly improved when applied according to the method of the second aspect. In addition, ruthenium contributes to the overall conductivity of the basic structural composition.
[0139] In this regard, it is preferred that the composition (i) applied in step (b) of the process comprises providing the composition (i) with an overall metal stoichiometry of Ru 0.3 (Sn+Ti) 0.7 This level of ruthenium is believed to be optimal in composition (i) of the method of the present invention to produce a particularly efficient and durable anode structure.
[0140] The combined presence of tin and titanium in addition to ruthenium in composition (i) leads, through its application in the process of the second aspect, to the formation of a structural base composition having the desired morphology of aggregated particles and the absence of extensive mud cracking behavior seen in other compositions comprising ruthenium and only titanium or tin. In this regard, a ruthenium content of at least 30 atomic % relative to tin and titanium in the starting composition (i) also leads under the conditions of the process to an enhanced formation of a network of aggregated particles in the morphology of the resulting structural base composition and the absence of cracking behavior.
[0141] The presence of tin in combination with ruthenium and titanium in composition (i) also contributes importantly to the long term durability of the anode prepared according to the second aspect and results in improved mechanical adhesion of the composite metallurgical layer to the anode substrate. The tin content in composition (i) can be further adjusted to provide a resulting anode having the desired overall stoichiometric ratio of Ru:Sn in the final anode structure and having the desired properties in this regard.
[0142] To optimize these advantages, it is preferred that tin and titanium are present in composition (i) in approximately equal amounts. Thus most preferably, the composition (i) applied in step (b) comprises Ru to provide an overall metal stoichiometry of Ru to composition (i). 0.3 Sn ≥ 0.3 Ti ≤0.4 , preferably Ru 0.3 Sn 0.35 Ti 0.35 Compounds of ruthenium, tin and titanium in varying amounts.
[0143] In all of the above embodiments of the second aspect, although minor amounts of other metal compounds may be present in addition to the essential ruthenium, tin and titanium compounds, it is preferred that composition (i) consists essentially of ruthenium, tin and titanium compounds, and more preferably, composition (i) consists of ruthenium, tin and titanium compounds, preferably in amounts that provide an overall metal stoichiometry of Ru in composition (i). 0.3 (Sn+Ti) 0.7 , most preferably providing an overall metal stoichiometry of Ru 0.3 Sn 0.35 Ti 0.35 .
[0144] In the method of the second aspect, in step (d) composition (iii) is applied to the metallurgical layer obtained by applying composition (i) or, with the optional application of composition (ii), by applying compositions (i) and (ii). Composition (iii) is an electrically conductive metallurgical catalyst precursor composition comprising crystalline cobalt oxide particles of the type described above in relation to the first aspect.
[0145] In this regard, it is preferred that the crystalline cobalt oxide particles in the catalyst precursor composition consist essentially of particles having the formula Co 3 O 4 In one such embodiment, the cobalt oxide crystalline particles may be composed of a crystalline cobalt oxide having the formula Co 3 O 4 The presence of this crystalline form of cobalt oxide can be confirmed by X-ray diffraction or other conventional crystallographic techniques.
[0146] In another more preferred embodiment, the cobalt oxide crystalline particles in the catalyst precursor composition consist essentially of a material having the chemical formula Co 3 O 4 In one embodiment, the catalyst precursor composition comprises a crystalline cobalt oxide having a composition of 100% by weight and further comprising ruthenium to a ruthenium content of up to 5 atomic % based on the total metal atomic content of the crystalline particles, at least some of which is present in the form of a surface decoration on the crystalline particles. In this latter embodiment, the crystalline cobalt oxide particles in the catalyst precursor composition may further contain crystalline regions in which, in addition to the surface decoration, ruthenium is incorporated into the crystal lattice of the cobalt oxide, or has formed a mixed metal oxide with cobalt, or both.
[0147] The limited amount of ruthenium combined with the cobalt oxide crystalline particles in the catalyst precursor composition provided in these embodiments provides the advantage of further improving the properties of the composite metallurgical layer when applied to the anode in the method of the present invention, most especially by improving the selectivity of the catalyst to the chlorine evolution reaction and improving the durability of the anode, especially in terms of operating life. At least in the case of incorporation into the lattice of cobalt oxide, ruthenium may exist in the form of an oxide compound or in the form of a metallic element. The ruthenium combined with the cobalt oxide catalyst in these embodiments may exist in an overall non-stoichiometric ratio, close to a mixture of elemental ruthenium and oxide-bound ruthenium.
[0148] However, for the ruthenium content associated with the crystalline particles in the catalyst precursor composition, it has been found that exceeding the upper limit of 5 atomic % leads to a reduction in the efficiency of the chlorine evolution reaction, especially for water treatment applications, as evidenced by a reduction in low salt efficiency. Therefore, the ruthenium content associated with the cobalt oxide catalytic particles should be limited to a specified level, and further increasing the ruthenium content is not advantageous in the expectation of further improvement.
[0149] In all of the above embodiments, it is preferred that the catalyst precursor composition consists essentially of crystalline particles of cobalt oxide distributed in a mixture with other metal oxides, which mixture, when applied by the method of the second aspect, produces a crystalline matrix of other metal oxides in the final catalyst composition of the anode of the invention. It is particularly preferred that these other metal compounds do not contain a significant amount or any amount of precious metal oxides other than those provided herein with respect to the present invention, such as palladium or iridium.
[0150] In a particularly advantageous embodiment, the process of the second aspect is carried out using composition (iii) as a catalyst precursor, wherein crystalline particles of cobalt oxide (preferably as described above) are dispersed in a mixture of antimony and tin compounds, wherein the overall molar ratio of cobalt: total amount of antimony and tin in composition (iii) is in the range of 20:80 to 80:20. This combination of antimony and tin compounds in composition (iii) produces a crystalline matrix of antimony and tin oxides when applied by the process of the second aspect, in which the crystalline particles of cobalt oxide are aggregated to obtain the desired morphology of the composite metallurgical layer.
[0151] In this preferred embodiment, it has also been found that, compared with the ratio outside the specified ratio range, the molar ratio of cobalt in the range specified for composition (iii): antimony and tin total amount provides the improved operation durability of the anode structure obtained by the method of the present invention, which is proved by keeping lower overpotential for a longer time. In addition, within the specified ratio range, the efficiency of the obtained catalytic anode to the chlorine evolution reaction is improved. In these respects, 20:80 and 80:20 cobalt: the molar ratio of antimony and tin total amount is preferred, and 60:40 to 40:60 range is more preferred, 50:50 ratio is most preferred and best, especially for obtaining the obtained anode with high CER efficiency and longer working life at low overpotential.
[0152] In the above preferred embodiment, it has also been found that the performance of the resulting anode can be further enhanced when prepared by the method of the second aspect using the following composition (iii): in the composition (iii), the ratio of cobalt: antimony and tin total amount is controlled as described above and wherein the antimony and tin compounds are present in an amount that provides an overall metal stoichiometric ratio of antimony: tin of at most 1:10, preferably at most 1:20 to the composition (iii). In addition, controlling the antimony / tin ratio in the composition (i) within this range by the method of the present invention results in the anode having a further improved efficiency for the chlorine evolution reaction.
[0153] More preferably in this highly advantageous embodiment of the method, the overall metal stoichiometry of antimony:tin in composition (iii) is at most 1:50, especially at most 1: 100. For achieving an improved efficiency of the chlorine evolution reaction, the optimal overall metal stoichiometry of antimony:tin in composition (iii) is 1:200.
[0154] Most preferably, composition (iii) has both a preferred range of the ratio of cobalt: antimony and tin total amount, and a preferred range of the overall metal stoichiometric ratio of antimony: tin. Such composition (iii) acts as a particularly effective catalyst precursor composition in the method of the second aspect of the invention, and results in the formation of an anode structure having a particularly effective combination of efficiency for the chlorine evolution reaction and high durability providing a longer working life at low overpotentials.
[0155] Therefore, in particular, it is preferred in the method of the second aspect that composition (iii) comprises crystalline cobalt oxide particles dispersed in a mixture of antimony and tin compounds, wherein the total molar ratio of cobalt: total antimony and tin is in the range of 20:80 to 80:20, and the overall metal stoichiometry of antimony: tin is at most 1:10, preferably at most 1:20. More preferably, composition (iii) comprises crystalline cobalt oxide particles dispersed in a mixture of antimony and tin compounds, wherein the total molar ratio of cobalt: total antimony and tin is in the range of 40:60 to 60:40, and the overall metal stoichiometry of antimony: tin is at most 1:50, preferably at most 1:100. Most preferably, composition (iii) comprises crystalline cobalt oxide particles dispersed in a mixture of antimony and tin compounds, wherein the total molar ratio of cobalt: total antimony and tin is 50:50, and the overall metal stoichiometry of antimony: tin is at most 1:100, preferably 1:200 or less, ideally in the range of 1:200 to 1:250.
[0156] These highly preferred embodiments of composition (iii) may further comprise the preferred embodiments of the above-described crystalline cobalt oxide particles, in particular consisting essentially of particles having the formula Co 3 O 4 The crystalline particles may more preferably also contain substantially ruthenium to a ruthenium content of up to 5 atomic % based on the total metal atomic content of the crystalline particles, at least some of which is present in the form of surface decoration on the crystalline particles. In this latter embodiment, the crystalline cobalt oxide particles in the catalyst precursor composition (iii) may further contain crystalline regions in which, in addition to the surface decoration, ruthenium is incorporated into the crystal lattice of the cobalt oxide, or has formed a mixed metal oxide with cobalt, or both.
[0157] Compositions (i), (ii) and (iii) used in the process of the first aspect can each be prepared from compounds known in the art for metal oxide catalyst preparation, which are mixed together in the presence of a process solvent in an appropriate ratio according to the teachings of the present invention. Although these compounds may include related metal oxide compounds where feasible, other compounds that allow better mixing or suspension and are oxidized under subsequent heat treatment of the process to produce the desired metal oxide in situ are generally used.
[0158] Thus, it is preferred in the process of the second aspect that the ruthenium, tin and titanium compounds present in composition (i), the tin and antimony compounds present in composition (iii) and the optional ruthenium compound in composition (ii) (if present) each comprise compounds other than oxide compounds; and wherein the application of heat, subsequent drying and heat treatment in process steps (b) and (d) and optional step (c) (if present) thermally decompose these compounds into one or more of their respective metal oxides or mixed metal oxide compounds within the composite metallurgical layer of the final anode structure.
[0159] In this regard, the ruthenium, tin and titanium compounds present in composition (i) preferably comprise, more preferably consist of, their respective halide compounds and / or complexes with acetylacetone; the tin and antimony compounds, when present in composition (iii), preferably comprise, more preferably consist of, their respective halide compounds; and when composition (ii) is applied, the ruthenium present therein preferably comprises, more preferably consists of, its respective halide compounds or one or more of its complexes with acetylacetone. These compounds provide for the appropriate dispersion of the metals in the composition used in the process, and are subsequently converted to their respective oxides under the conditions of the process of the invention to produce the desired anode of the first aspect of the invention.
[0160] The starting composition for the process may additionally comprise other metal compounds as detailed under the first aspect which bring further advantages to the resulting anode.
[0161] Thus, the starting composition may additionally comprise at least one palladium compound in an amount providing a total palladium content of preferably at most 7 atomic %, preferably at most 5 atomic %, based on the total metal atomic content of the starting composition. Preferably, the starting composition (iii) additionally comprises at least one palladium compound in an amount providing a total palladium content of preferably at most 7 atomic %, preferably at most 5 atomic %, based on the total metal atomic content of the starting composition.
[0162] Composition (iii) may additionally comprise at least one copper compound, or at least one aluminum compound, or both, in amounts to provide composition (iii) with a total copper content of at most 10 atomic %, preferably at most 2 atomic %, based on the total metal atomic content of the composition, or a total aluminum content of at most 30 atomic %, preferably at most 20 atomic %, based on the total metal atomic content of the composition, or a total nickel content of at most 15 atomic %, preferably at most 10 atomic %, based on the total metal atomic content of the composition, or more than one of these.
[0163] At least one of the compositions (i), (ii) or (iii) may additionally comprise at least one iridium compound in an amount which provides a total iridium content of at most 15 atomic %, preferably at most 10 atomic %, respectively.
[0164] These additional metal species may be introduced via compounds which are conventionally used in the art for inclusion in metallurgical coatings.
[0165] In a further preferred embodiment, the starting composition (iii) does not contain any titanium compounds, so that a titanium-free catalyst composition having the above-mentioned attendant advantages is produced by the process of the second aspect.
[0166] In the method of the present invention, as detailed in the first aspect of the present invention, the electrically conductive solid substrate consists essentially of a valve metal, preferably titanium.
[0167] In the process of the present invention, the metallurgical compositions applied in steps (b) and (d) and optional step (c) (if present) can be applied sequentially by coating techniques known in the art, such as brushing, rolling or drawdown, spraying (by means such as electrospraying or pressure spraying), dipping and curtain coating. Where desired, thicker coatings can be applied by multiple-pass coating techniques on the underlying structure.
[0168] Preferably, each metallurgical composition applied in steps (b) and (d) and optional step (c) (if present) is applied sequentially by brushing one or more passes on the underlying structure, or by spraying one or more passes on the underlying structure. However, other conventional techniques may be used to apply one or more metallurgical compositions.
[0169] The third aspect of the present invention (chlorine electrolysis system)
[0170] In a third aspect, the present invention provides an electrolytic chlorine production system, comprising the electrolytic anode structure of the first aspect or the electrolytic anode structure obtainable by the method of the second aspect.
[0171] Fourth Aspect of the Invention (Electrolysis Method)
[0172] In a fourth aspect, the present invention provides an electrolytic method for catalyzing the precipitation of chlorine gas from an aqueous solution containing chloride ions, comprising passing an electric current through the solution in an electrolytic cell comprising the electrolytic anode structure of the first aspect or the electrolytic anode structure obtainable by the method of the second aspect, wherein chlorine gas is precipitated from the aqueous solution at the anode.
[0173] In a preferred aspect of the electrolytic process, the chlorine gas evolved by the process is used as a biocide to disinfect water, more particularly for disinfecting ballast water or industrial wastewater, or municipal or domestic water, such as recreational water in swimming pools and domestic drinking water. In an alternative preferred aspect, the process is a chlor-alkali process for generating and recovering chlorine gas.
[0174] Working Example of the Invention
[0175] 1. Preparation Example
[0176] Preparation of Exemplary Starting Compositions for Use in the Methods of the Invention
[0177] 1.A Exemplary starting compositions (i), (ii) and (iii) for steps (b), (c) and (d), respectively, of the process are prepared from the following component compounds and liquids available in the art:
[0178] Crystalline solid compounds:
[0179] RuCl 3. xH 2 O (available as a commercial product from Sigma-Aldrich),
[0180] SnCl 4. 5H 2 O (available as a commercial product from Sigma-Aldrich),
[0181] SbCl 3 (available as a commercial product from Sigma-Aldrich),
[0182] PdCl 2 (available as a commercial product from Alfa Aesar), Ru(acac) 3 (available as a commercial product from Sigma-Aldrich; wherein "acac" stands for acetylacetone), and having the chemical formula Co 3 O 4 Crystalline cobalt oxide particles were synthesized according to the procedure outlined in Section 1.D below.
[0183] liquid:
[0184] 2-Propanol (also known as isopropanol, available as a commercial product from Alfa Aesar), deionized water,
[0185] TiCl 3 Solution (TiCl 3 Available as a commercial product from Sigma-Aldrich (Sigma-Aldrich) as a 12% solution in aqueous hydrochloric acid.
[0186] 1.B Preparation of the starting composition (i) of the method
[0187] The structural base composition having an overall metal stoichiometry of Ru used in the method of forming a composite metallurgical layer is prepared according to the following sequence: 0.3 Sn 0.35 Ti 0.35 A preferred composition (i) consists essentially of ruthenium, tin and titanium compounds.
[0188] Add RuCl to the 70 mL vial. 3 .xH 2 O (207.6 mg; 1 mmol) and SnCl 4 .5H 2 O (409.4 mg; 1.17 mmol). These solid materials were dissolved in 2-propanol (17 mL) by vortexing until no metal precursor settled on standing. To the resulting solution was added 1.5 mL of TiCl by dropwise addition under mechanical stirring at 1,000 rpm. 3 Solution (12% TiCl 3 HCl solution, 1.17 mmol). In addition, 1.5 ml of deionized water was added dropwise to the solution. The resulting solution was aged for 5 hours under ambient conditions with mechanical stirring at 1,000 rpm to produce composition (i) for use in the method of the present invention.
[0189] 1.C Preparation of the starting composition (ii) of the method
[0190] A preferred composition (ii) consisting essentially of ruthenium dioxide for use in the method of forming the optional intermediate layer is prepared according to the following sequence.
[0191] A solvent was prepared by mixing 2-propanol (38.7 mL) and deionized water (7.8 mL). 15.5 mL of the prepared solvent was then placed in a 70 mL vial, to which 115.8 mg (0.29 mmol) of Ru(acac) was added. 3 and an additional 2 ml of IPA. The solution thus prepared was then sonicated for 20 minutes to produce composition (ii) for use in the method of the present invention.
[0192] 1.D Preparation of the starting composition (iii) of the method
[0193] A preferred catalyst precursor composition (iii) consisting essentially of crystalline particles of cobalt oxide for use in this process as a composition of the catalyst composition for forming a composite metallurgical layer is prepared according to the following sequence.
[0194] a)Co 3 O 4Synthesis of crystalline particles
[0195] Co(NO 3 ) 2 6H 2 ZrO (170 g, 0.584 mol) was dissolved in ethanol (99.9%, 510 ml). 1-Heptanol (510 ml) was added to this mixture and the mixture was stirred for 5 minutes. The mixture was transferred to a pressure reactor and heated at 160°C for 7 hours. The resulting mixture was allowed to stand for 16 hours to cool to room temperature and allow the solid product to settle. The resulting supernatant was decanted and the resulting solid product was washed three times with isopropanol (100 ml). Between each wash, the product was thoroughly mixed and then centrifuged at 8500 rpm for 1 hour. The supernatant was decanted and removed in each case. Isopropanol (IPA) was added to meet a solid content of 12 wt % (the amount of IPA added was calculated by the resulting density of the solution once mixed). The resulting mixture was heated to 40°C with a mixture containing 0.5 mm ZrO. 2 The beads were ball milled at 2000 rpm at room temperature for 2 h to produce 12 wt% Co 3 O 4 Nanoparticle solution.
[0196] The Co synthesized above 3 O 4 The crystalline particles were sized by direct measurement of the diameter in transmission electron microscopy images and were found to be between 3 nm and 7 nm in diameter with a median diameter of 5 nm.
[0197] b) Preparation of composition (iii)
[0198] The solvent was prepared by mixing 2-propanol (38.7 mL) and deionized water (7.8 mL). 3 (44.7 mg; 0.20 mmol) was dissolved in this solvent by vortexing. 5 mL of the solution thus prepared was then diluted with an additional 45 mL of the solvent mixture to form a first "antimony solution". 15.5 mL of this antimony solution was then mixed with SnCl 4 .5H 2 O (457.8 mg; 1.31 mmol) was mixed under vortex to form an "antimony-tin solution".
[0199] PdCl 2 (4.8 mg; 0.027 mmol) was placed in a 70 ml vial, and then the prepared antimony-tin solution was poured into the vial. In addition, 1 ml of the Co prepared in a) above was added. 3 O 4The crystalline particle solution (0.438 mmol) and 1 ml of 2-propanol were each added to the solution. Finally, the mixture was sonicated for 20 minutes to produce a composition (iii) for use in the method of the present invention, which comprises Co with a palladium content of 1 atomic % in a solution of antimony and tin compounds. 3 O 4 Crystalline particles wherein the molar ratio of antimony:tin is 1:247 and the overall metal stoichiometry of cobalt:total antimony and tin is 50:50.
[0200] The catalytic anode of the present invention is prepared by the method of the present invention
[0201] The method according to the second aspect of the present invention is as follows to prepare the anode according to the first aspect of the present invention.
[0202] A titanium mesh was obtained as an anode substrate and, after cleaning, was heated to a temperature of 100° C. using a hot plate. At this temperature, the composition (i) prepared above was applied to the hot substrate surface by brushing. The resulting coated sample was kept at 100° C. for 1 minute, the substrate was turned over and the reverse side was coated again, and the substrate was kept at 100° C. for 1 minute. The coated sample was then transferred to a 500° C. oven for 5 minutes. The coated sample was then transferred back to the hot plate at 100° C., and the coating and heat treatment steps were repeated. This brushing of the substrate surface with composition (i) was repeated another four times, so that a total of five brushings were applied on the surface.
[0203] The resulting structure was then further coated with the composition (ii) prepared above in the same manner as described above, for a total of five passes on the surface. The resulting structure was thereafter further coated with the composition (iii) prepared above, for a total of 10 passes on the surface with this catalyst precursor composition. After these coating steps, the resulting coated structure was dried at the same temperature.
[0204] Then, the dried resultant structure was finally heat treated in an oven at 500° C. for 1 hour, followed by slow cooling in the oven for 8 hours to obtain the anode structure of the present invention.
[0205] Three further examples were prepared according to the general procedure described above, however, in order to separate the metallic composition of the resulting composite metallurgical layer, a glass substrate was used instead of the titanium substrate of the above examples, and compositions (i), (ii) and (iii) were applied by spraying. In the case of Example 1 below, three spraying passes were used to apply each of compositions (i), (ii) and (iii), wherein composition (i) was sprayed at a rate of 300 μL / min and compositions (ii) and (iii) were sprayed at a rate of 600 μL / min. In the case of Example 2 below, three spraying passes were also used to apply each of compositions (i) and (ii), and six spraying passes were used to apply composition (iii), wherein compositions (i) and (ii) were sprayed at a rate of 300 μL / min and composition (iii) was sprayed at a rate of 600 μL / min. In the case of Example 3 below, three spray passes were also used to apply each of compositions (i), (ii) and (iii), wherein compositions (i) and (ii) were sprayed at a rate of 600 μL / min and composition (iii) was sprayed at a rate of 300 μL / min. The resulting composite metallurgical layers were then each analyzed multiple times using the ICP-MS technique, and the following metal composition information was obtained, expressed in atomic % of the total metal atomic content:
[0206]
[0207]
[0208] In each case, the resulting composite metallurgical layer contains cobalt as the main metal component, constituting an average of at least 65 atomic % of the total metal atomic content of the composite metallurgical layer. The average overall metal stoichiometric ratio of cobalt: antimony and tin total provides a value in the most preferred range of 3:1 to 5:1 in each case, and the overall metal stoichiometric ratio of antimony: tin is also in the preferred ratio range of this feature in each case, with the samples giving values of 1:75, 1:84 and 1:31, respectively. The overall stoichiometric ratio of ruthenium: tin in the composite metallurgical layer is also in the most preferred range of this feature of 1:≥5 in each case, being 1:8, 1:15 and 1:6, respectively.
[0209] Figure 4 A typical concentration-depth profile of the metal distribution through the thickness of an in-situ composite metallurgical layer prepared according to the above method is provided, showing a preferred non-uniform distribution of cobalt oxide through the thickness of the composite metallurgical layer, being higher towards the outer surface.
[0210] 2. Performance Examples
[0211] The following experimental techniques were used to demonstrate the performance and advantages of the anode of the present invention.
[0212] Chlorine evolution reaction (CER) efficiency test:
[0213] The Faradaic efficiency of an electrolytic cell provides an important measure of the efficiency of the catalytic anode for the CER reaction.
[0214] An electrolytic cell was set up in which the counter electrode (cathode) and the working electrode (anode according to the invention) were configured as follows.
[0215] 5x 15cm 2 The Ti mesh counter electrode was etched with 2.0 M sulfuric acid at 60° C. for 1 hour until the etching solution turned light purple. The etched Ti mesh was then ultrasonically treated with 95% pure ethanol for 10 minutes several times. The rinsed Ti mesh was dried by blowing nitrogen. The dried counter electrode was then masked with silicon tape and electroplating tape to leave a 5 x 5 cm 2 area.
[0216] The anode prepared according to the present invention was also masked with silicon tape and electroplating tape to leave a 1 x 5 cm 2 Masking the electrodes helps to focus the current into a confined area of the electrode exposed to the electrolyte, thus increasing the current density and speeding up the test.
[0217] The electrolytic cell was assembled by attaching a masked counter electrode to one side of an electrode frame and a working electrode to the opposite side of the frame. At the bottom end of both electrodes, a portion of the frame maintained a gap of 5 mm between the electrodes.
[0218] The above test cell was configured and operated under the following conditions:
[0219] a) Pour 500 ml of 20 mM NaCl solution into a 500 ml beaker. Place the electrode cell assembled above in the beaker and connect two wires to the working electrode and the counter electrode respectively.
[0220] b) Stir the solution at 300 rpm using a magnetic stir bar. The connected potentiostat is then set at 40 mA / cm 2 The assay was run in chrono-potentiometry mode for 1 min.
[0221] c) After 1 minute of operation, the active chlorine concentration was measured and compared with the theoretical concentration obtained from the initial chloride ion concentration to determine the Faradaic efficiency (FE) of the electrolytic cell containing the working electrode (anode of the present invention).
[0222] Active chlorine concentration is measured by one of two interchangeable methods:
[0223] Active chlorine concentration measured by DPD colorimetry
[0224] In this method, the DPD vials were washed with DI water until initial testing confirmed the absence of residual active chlorine in the test vials.
[0225] After the electrolyzer was run for 1 minute, the solution was stirred at 600 rpm for 1 minute to make a completely uniform test solution. Then 1 ml of this well-mixed solution was diluted to 1 / 10 with 20 mM NaCl solution in a DPD vial to obtain a test solution volume of 10 ml. The DPD reagent was then added to the DPD vial and the vial was vortexed for 10 seconds. The active chlorine concentration was then measured with a DPD pocket colorimeter and the Faraday efficiency (FE) was calculated by dividing the amount of active chlorine generated by the theoretical amount of active chlorine generated.
[0226] Determination of active chlorine content by iodometric titration
[0227] After the electrolyzer was run for 1 minute, the solution was stirred at 300 rpm to make a uniform solution. Then 1.6 grams of KI (potassium iodide) were added to the beaker containing the solution. After adding KI, the solution became light yellow. After adding 4 milliliters of glacial acetic acid to the solution, the solution became light orange. After 4 milliliters of starch solution were added to the beaker, the solution became dark blue. The dark blue solution was then titrated with 0.02N sodium thiosulfate until the solution became colorless, and the amount of active chlorine generated was estimated by the titration of the sodium thiosulfate added. The Faraday efficiency was calculated again by dividing the amount of active chlorine generated by the theoretical amount of active chlorine generated.
[0228] Chlorine evolution reaction (CER) life test:
[0229] The Faradaic efficiency of an electrolyser, measured regularly during long-term testing, provides important evidence of the lifetime of the catalytic anode and hence the durability of the anode for CER reactions. A rapid increase in FE signifies degradation of the anode and indicates that it is approaching the end of its durability for CER.
[0230] The electrolytic cell with counter and working electrodes was configured as described above. For experimental acceleration purposes, the working electrode (anode) was masked to 1 cm 2 To concentrate the current density. Masking was done by applying silicon tape, covered with plating tape. The top of the working electrode was also grounded back to the metal substrate before connection.
[0231] a) Pour 1 liter of 0.6 M NaCl solution into a beaker surrounded by a cooling jacket, which maintains the test solution at 15° C. After allowing the temperature to stabilize for 1 hour, place the electrode cell assembled above in the beaker and connect two wires to the working electrode and the counter electrode, respectively.
[0232] b) Stir the solution at 300 rpm using a magnetic stir bar. The connected potentiostat is then set at 500 mA / cm2 under stirring conditions at 300 rpm. 2 The experiment was run in chrono-potentiometry mode until an increase of more than 12 V was recorded, at which point the result was taken as the duration of the experiment.
[0233] c) During the run, the cell potential is repeatedly measured and plotted over time to report the potential for the CER over the duration of the life test and to identify the degradation point, where the potential increases rapidly and exceeds the useful life of the anode (considered as such when a voltage exceeding 12 V is recorded).
[0234] Mechanical adhesion test
[0235] The mechanical adhesion of the metallurgical surface layer of the anode is evaluated by the following method. A piece of 3M electroplating tape is placed on a part of the working electrode (tested anode) that is not masked by the preparation described in detail above. Apply slight pressure with a pipette head so that the tape is gradually in close contact with the electrode surface coated. Then peel off the tape, and visually evaluate the extent that the residue of the metallurgical coating is retained on the adhesive surface of the stripping tape, as a measure of the adhesion strength of the coating to the electrode substrate, the residue on the removed tape shows that the residual adhesion to the substrate is lower.
[0236] Acid stability test
[0237] Prepare a 5 wt% hydrochloric acid solution by diluting concentrated hydrochloric acid with deionized water to the required amount. Cut the anode to be tested into a size of 2 cm x 1 cm and place it in a 10 ml vial, to which 5 ml of the 5% hydrochloric acid solution is added so that the anode sample is completely immersed. Observe the color of the sample and the acid solution over time.
[0238] 2.1 Benefits of the structural base composition of the present invention
[0239] The structural base composition of the anode of the present invention is derived in the accompanying method of the second aspect of the present invention to provide the overall metal stoichiometry Ru to the composition (i). ≥0.3 (Sn+Ti) ≤0.7 The importance of these defining features in the process of the present invention is demonstrated as follows.
[0240] 2.1(a) Necessity of a ruthenium metal stoichiometry of 0.3 or more moles:
[0241] Figure 5 The results of CER life tests conducted according to the above test method are reported. In each case, the working electrode (tested anode) was prepared similarly to the preparation method given in Part 1 of the Examples, but only the base composition (i) was applied to the substrate, omitting compositions (ii) and (iii). Three comparative examples of this type were prepared by varying the amount of ruthenium added to composition (i) and keeping the tin and titanium components as the balance of each composition in a 1:1 stoichiometric ratio.
[0242] like Figure 5 As shown in, the CER lifetime results indicate that when ruthenium is present at a stoichiometric level below 0.3, a low overpotential is not maintained for a long time. In order to avoid the structural base composition from weakening the potential efficiency and durability of the catalytic anode for the CER reaction, a specified stoichiometry is required, wherein ruthenium is present in composition (i) at least at a stoichiometric level of 0.3.
[0243] This ruthenium stoichiometry also ensures that the desired morphology of the structural base composition is obtained - as a layer of aggregated particles interspersed with voids, onto which the catalyst composition can then be advantageously applied. The ruthenium stoichiometry of 0.3 in composition (i) ensures that the resulting structure exhibits a defined crystalline structure by XPS and defined, connected particles when imaged using SEM.
[0244] 2.1(b) Necessity of the Ru / Sn / Ti ternary structural base composition:
[0245] Figure 6 The results of CER life tests conducted according to the above test method are reported.
[0246] In each case, the working electrode (tested anode) was prepared using a preparation method similar to that given in Part 1 of the Examples, applying the base composition (i) and the catalyst precursor composition (iii) to the substrate, omitting the optional composition (ii). Each example was prepared using the same catalyst precursor composition (i) of the preferred type prepared in Part 1 of the Examples, which consisted of crystalline Co in a mixture of antimony and tin compounds. 3 O 4 The composition further comprises 5 atomic % of ruthenium and 1 atomic % of palladium.
[0247] However, the underlying structural base composition in these experiments was varied. One example (of the invention) was prepared using a composition (i) of the type also exemplified in Section 1 above, having an overall metal stoichiometry of Ru 0.3 Sn 0.35 Ti 0.35 Two comparative examples were prepared by varying composition (i) to exclude titanium or tin compounds and keeping the ruthenium at an overall metal stoichiometry of 0.3. Thus, this series of tests compares the effect of combining ruthenium with tin and / or titanium at equal ruthenium contents.
[0248] like Figure 6 As shown in , the CER life results show that the ternary combination of ruthenium, tin and titanium allows the low overpotential to be maintained for a much longer time in the presence of the same catalyst composition of the present invention. Comparative examples lacking tin or titanium result in shorter lives and do not provide the same advantageous performance.
[0249] Mechanical adhesion tests were also conducted to compare anodes made from the ternary metal composition (i) according to the invention with a comparative example in which the binary metal composition (i) contained only ruthenium and tin. Excellent mechanical adhesion of the metallurgical coating to the substrate surface was observed for the invention, as evidenced by the lower degree of coating residue visible on the removed tape.
[0250] like Figure 7 SEM examination after application of the basecoat as shown in also revealed extensive mud cracking on the sediment-like outer surface of the basecoat in the case of the ruthenium / tin comparative base composition. In contrast, the basecoat made from the ternary base composition of the present invention exhibited a coating of aggregated particles interspersed with voids.
[0251] exist Figure 8 In the case of a Co doped with a ruthenium compound 3 O 4 Electrodes having a catalyst layer formed of crystalline nanoparticles ("NPs") show lifetime advantages resulting from the presence of the structural base layer of the present invention. The cell potential is initially at a lower level over the lifetime of the electrode and exhibits a significantly lower rate of increase (indicating an increased overpotential) when the structural base layer is also present as an intermediate layer between the electrode substrate and the catalyst composition.
[0252] 2.2 Additional advantages of the optional composition (ii) of the present invention
[0253] The optional intermediate layer provided by application of composition (ii) in a preferred method aspect of the invention provides further improvement in the properties of the finished anode. Fig. 9A lifetime comparison between two anodes of the present invention is shown. The two anodes share the same, preferred structural base composition, but one incorporates ruthenium into the catalyst composition according to the working examples in Section 1 above, while the other instead incorporates ruthenium as RuO 2 Incorporated into the optional interlayer composition (ii). The latter anode exhibits improved lifetime in terms of maintaining lower potentials for longer periods of time.
[0254] 2.3 Benefits of the Catalyst Composition of the Invention
[0255] The importance of catalyst composition to performance is described below.
[0256] 2.3(a) Preferred tin and antimony oxide matrices included in the catalyst composition
[0257] exist Fig.10 and 11 The advantageous presence of tin and antimony in a specified stoichiometric ratio is shown in FIG. Similar anodes were also prepared according to the examples in Section 1 above, but using catalyst compositions whose tin and antimony contents were varied as shown in the figure. In each case, lifetime or CER efficiency tests were performed and the (over)potentials were compared over time.
[0258] like Fig.10 It was demonstrated that the overall metal stoichiometric ratio of cobalt: antimony and tin in composition (iii) has an impact on the life of the anode; anode structures made from catalyst precursor compositions wherein the ratio is in the range of 20:80 to 80:20, preferably 50:50, exhibit improved durability in maintaining low potential over a longer operating life. A molar ratio of 50:50 provides the best results.
[0259] like Fig.11 (a) As demonstrated by 0.3 Sn 0.35 Ti 0.35 The structural base composition (i) is composed of ruthenium, tin and titanium compounds and the different solutions of antimony and tin compounds contain Co 3 O 4 Among the electrodes of the present invention of various catalyst precursor compositions (iii) of crystalline particles, the electrodes from the embodiments in which the antimony and tin compounds are present in amounts providing the composition (iii) with an overall metal stoichiometric ratio of antimony:tin of up to 1:20 show the greatest advantage in CER efficiency as measured by the Faraday efficiency (FE) using the method detailed earlier in this specification, with increasing advantages at ratios of 1:20, 1:50, 1:100 and 1:200, the latter being the most efficient composition (iii), to yield an anode with the highest efficiency.
[0260] like Fig.11 As demonstrated by (b), the life of the electrode in which the antimony and tin compounds are present in an amount to provide composition (iii) with an overall metal stoichiometry of antimony:tin of at most 1:20 shows improvement over the examples in which the ratio of antimony:tin is 1:3 or 1:6.5.
[0261] 2.3(b) Including palladium oxide in the catalyst composition
[0262] In a further experiment, the anode was directly coated with a catalyst composition (iii) containing cobalt oxide particles, ruthenium oxide and tin and antimony oxides according to the invention, and the effect of introducing palladium as a further component was evaluated. The results are shown in the following table, which demonstrates the efficiency improvement brought about by the preferred inclusion of a small amount of palladium in the catalyst composition.
[0263]
[0264] 2.3(c) Inclusion of iridium in the catalyst composition
[0265] Further electrodes were prepared generally according to the preparation method given in Part 1, but using different stoichiometric ratios of cobalt: antimony and total tin and excluding palladium from catalyst precursor composition (iii), introducing iridium instead, to show the advantages brought by the inclusion of this other metal. These examples are given in the table below.
[0266] In each case, the Faradaic efficiency was measured in 20 mM NaCl solution according to the method described above.The results show that further efficiency advantages are obtained by including small amounts of iridium in the electrodes of the invention.
[0267]
[0268] The above examples illustrate the high performance of specific embodiments of the present invention.
Claims
1. A catalytic anode structure for an electrolytic chlorine production system, comprising a conductive solid substrate, on the surface of the substrate facing the electrolyte, covered with a conductive composite metallurgical layer, the layer comprising: a structural base composition coating the surface of the substrate, the structural base composition having the morphology of aggregated particles interspersed with voids and comprising metal oxide compounds of ruthenium, tin and titanium; and a catalyst composition comprising crystalline particles of cobalt oxide distributed on the upper surface of the structural base composition and within the voids of the structural base composition; and wherein cobalt is present in an amount of at least 12.5 atomic % of the total metal atomic content of the composite metallurgical layer; and ruthenium and tin are present in amounts to provide the composite metallurgical layer with an overall metal stoichiometric ratio of Ru:Sn of 1:≥1 based on the total content of ruthenium and tin in the composite metallurgical layer; and The outer surface of the composite metallurgical layer has the morphology of a continuous coating of aggregated particles.
2. The anode structure of claim 1 , wherein cobalt is present in an amount of at least 40 atomic % of the total metal atomic content of the composite metallurgical layer; and ruthenium and tin are present in an amount to provide the composite metallurgical layer with an overall metal stoichiometric ratio of Ru:Sn of 1:≥5 based on the total content of ruthenium and tin in the composite metallurgical layer.
3. The anode structure of claim 1 or claim 2, wherein the cobalt oxide crystalline particles in the catalyst composition are substantially composed of a chemical formula of Co 3 O 4 Composition of crystalline cobalt oxide.
4. The anode structure according to any one of claims 1 to 3, wherein the catalyst composition further comprises one or more noble metals or compounds thereof, preferably ruthenium or an oxide thereof.
5. The anode structure of claim 4, wherein the cobalt oxide crystalline particles in the catalyst composition are substantially composed of a particle having a chemical formula of Co 3 O 4 The invention relates to a crystalline cobalt oxide composition of the present invention and further comprises essentially ruthenium or its oxide to a ruthenium content of up to 5 atomic % based on the total metal atomic content of the crystalline particles, at least some of the ruthenium being present in the form of surface decoration on the crystalline particles.
6. The anode structure of claim 5, wherein the crystalline cobalt oxide particles in the catalyst composition further contain crystalline regions in which ruthenium is incorporated into the crystal lattice of the cobalt oxide, or has formed a mixed metal oxide with cobalt, or both.
7. An anode structure according to any one of claims 1 to 6, wherein the catalyst composition comprises crystalline particles of cobalt oxide within a crystalline matrix of antimony and tin oxides; the catalyst composition is present on the upper surface of the structural base composition and within the voids of the structural base composition.
8. The anode structure of claim 7, wherein the overall metal stoichiometry of cobalt: total antimony and tin in the composite metallurgical layer is in the range of 2:1 to 9:
1.
9. An anode structure according to claim 7 or 8, wherein the antimony and tin compounds are present in an amount to provide the composite metallurgical layer with an overall metal stoichiometry of antimony:tin in the range of 1:5 to 1:200, preferably in the range of 1:5 to 1:
100.
10. Anode structure according to any one of claims 4 to 9, wherein the composite metallurgical layer further comprises at least one palladium compound in an amount providing the composite metallurgical layer with a total palladium content of at most 7 atomic %, preferably at most 3 atomic %, of the total metal atomic content of the composite metallurgical layer.
11. Anode structure according to any one of claims 1 to 10, wherein the electrically conductive solid substrate consists essentially of a valve metal, preferably titanium.
12. The anode structure of any one of the preceding claims, wherein the cobalt of the catalyst composition is non-uniformly distributed throughout the thickness of the composite metallurgical layer, the concentration of cobalt oxide in the composite metallurgical layer being higher adjacent its outer surface than adjacent the substrate surface.
13. The anode structure of any one of claims 1 to 12, wherein the composite metallurgical layer comprises ruthenium oxide distributed throughout or substantially distributed throughout the base structure composition and the catalyst composition.
14. Anode structure according to any one of claims 1 to 13, wherein the structural base composition consists of metal oxide compounds of ruthenium, tin and titanium.
15. An anode structure according to any one of claims 1 to 14, wherein the base structure composition or the catalyst composition or both further comprises iridium, in the form of its oxide or other catalytically active species, in an amount providing a total iridium content of at most 15 atomic %, preferably at most 5 atomic %, of the total metal atomic content of the composite metallurgical layer.
16. An anode structure according to any one of claims 1 to 15, wherein the composite metallurgical layer further comprises at least one copper compound in an amount such that the composite metallurgical layer provides a total copper content of at most 10 atomic % of the total metal atomic content of the composite metallurgical layer, preferably at most 2 atomic %; or at least one aluminum compound in an amount such that the layer provides a total aluminum content of at most 30 atomic % of the total metal atomic content of the composite metallurgical layer, preferably at most 20 atomic %; or at least one nickel compound in an amount such that the layer provides a total nickel content of at most 15 atomic % of the total metal atomic content of the composite metallurgical layer, preferably at most 10 atomic %; or more than one of these.
17. The anode structure of any one of claims 1 to 16, wherein the outer surface of the composite metallurgical layer has the morphology of a continuous uncracked coating of aggregated particles.
18. The anode structure according to any one of claims 1 to 17, wherein the catalyst composition of the composite metallurgical layer does not contain titanium or compounds thereof.
19. A method for preparing a catalytic anode structure for an electrolytic chlorine production system, comprising the following sequential steps: a) preparing or obtaining a conductive solid substrate; b) applying to the electrolyte-facing surface of the substrate a conductive metallurgical composition (i) comprising providing the composition (i) with an overall metal stoichiometry of Ru ≥0.3 (Sn+Ti) ≤0.7 Compounds of ruthenium, tin and titanium in amounts; c) optionally applying an electrically conductive metallurgical composition (ii) comprising one or more ruthenium compounds on the metallurgical layer obtained by applying the composition (i); and (d) applying an electrically conductive metallurgical catalyst precursor composition (iii) comprising crystalline cobalt oxide particles on the metallurgical layer obtained by applying composition (i) or, with the optional application of composition (ii), by applying compositions (i) and (ii); wherein the process solvent used to apply the metallurgical composition in steps (b) and (d) and optionally step (c) is a mixture of isopropanol and water in a ratio ranging from 80:20 to 95:5 by volume; and Therein, the resulting structure is subsequently dried and then heat treated at a temperature of at least 450° C.
20. A method according to claim 19, wherein during steps (b) and (d), and during step (c) when present, the substrate (a) is heated to a temperature in the range of 50-200°C and the resulting structure is thereafter dried at a temperature in said same range.
21. A method according to claim 20, wherein throughout steps (b) and (d), and throughout step (c) when present, the substrate (a) is heated to a temperature of 100°C and the resulting structure is thereafter dried at said temperature.
22. The method according to any one of claims 19 to 21, wherein after drying, the heat treatment temperature is in the range of 450 to 550°C.
23. The method according to any one of claims 19 to 21, wherein the heat treatment temperature is 500°C.
24. A method according to any one of claims 18 to 23, wherein the process solvent used to apply the metallurgical composition in steps (b) and (d) and optionally step (c) is a mixture of isopropanol and water in a ratio in the range of 85:15 by volume.
25. A method according to any one of claims 19 to 24, wherein in steps (b) and (d), and in optional step (c) when present, each metallurgical composition applied is applied sequentially by brushing on the underlying structure in one or more passes.
26. A method according to any one of claims 19 to 24, wherein in steps (b) and (d), and in optional step (c) when present, each metallurgical composition applied is applied sequentially by spraying one or more passes onto the underlying structure.
27. A method according to any one of claims 19 to 26, wherein the composition (i) applied in step (b) comprises providing the composition (i) with an overall metal stoichiometry of Ru 0.3 (Sn+Ti) 0.70 Compounds of ruthenium, tin and titanium in varying amounts.
28. The method of claim 27, wherein the composition (i) applied in step (b) comprises providing the composition (i) with an overall metal stoichiometry of Ru 0.3 Sn 0.35 Ti 0.35 Compounds of ruthenium, tin and titanium in varying amounts.
29. A method according to any one of claims 19 to 28, wherein the crystalline cobalt oxide particles in the composition (iii) applied in step (d) consist essentially of a material having the formula Co 3 O 4 Composition of crystalline cobalt oxide.
30. The method of claim 29, wherein the cobalt oxide crystalline particles in composition (iii) further comprise ruthenium in an amount of up to 5 atomic % of ruthenium based on the total metal atomic content of the crystalline particles, at least some of the ruthenium being present in the form of surface decoration on the crystalline particles.
31. A method according to claim 29 or claim 30, wherein the crystalline cobalt oxide particles in composition (iii) further contain crystalline regions in which some of the ruthenium has been incorporated into the crystal lattice of the cobalt oxide, or has formed a mixed metal oxide with cobalt, or both.
32. A method according to any one of claims 19 to 31, wherein in the composition (iii) applied in step (d), the crystalline cobalt oxide particles are dispersed in a mixture of antimony and tin compounds, wherein the overall metal stoichiometric ratio of cobalt: total amount of antimony and tin in composition (iii) is in the range of 20:80 to 80:20, and is preferably 50:
50.
33. A method according to claim 32, wherein in composition (iii), the antimony and tin compounds are present in an amount to provide composition (iii) with an overall metal stoichiometry of antimony:tin of at most 1:10, preferably at most 1:
20.
34. The method of claim 33, wherein the antimony and tin compounds are present in the composition (iii) applied in step (d) in an amount to provide the composition (iii) with an overall stoichiometric ratio of antimony:tin of 1:200 or less.
35. The method according to any one of claims 19 to 34, wherein the composition (iii) further comprises at least one palladium compound in an amount to provide the composition (iii) with a total palladium content of preferably at most 7 atomic %, preferably at most 5 atomic %, based on the total metal atomic content of the composition (iii).
36. A method according to any one of claims 19 to 35, wherein the ruthenium, tin and titanium compounds present in composition (i), the tin and antimony compounds present in composition (iii) and the ruthenium compound present in optional composition (ii) each comprise compounds other than oxide compounds; and wherein their heat treatment and, if present, their heating in steps (b) and (d) and optional step (c) are applied such that these compounds thermally decompose into one or more of their respective metal oxides or mixed metal oxide compounds within the composite metallurgical layer of the final anode structure.
37. A method according to claim 36, wherein the ruthenium, tin and titanium compounds present in composition (i) comprise, and preferably consist of, their respective halide or sulfate compounds and / or complexes with acetylacetone; and wherein the tin and antimony compounds, when present in composition (iii), comprise, and preferably consist of, their respective halide or sulfate compounds; and wherein when composition (ii) is applied, the ruthenium present therein comprises, and preferably consists of, its respective halide compound or complexes with acetylacetone.
38. The method according to any one of claims 19 to 37, wherein the composition (iii) further comprises at least one copper compound, or at least one aluminum compound or at least one nickel compound, or more than one of these, in amounts to provide the composition (iii) with a total copper content of at most 10 atomic %, preferably at most 2 atomic %, based on the total metal atomic content of the composition (iii); or a total aluminum content of at most 30 atomic %, preferably at most 20 atomic %, based on the total metal atomic content of the composition (iii); or a total nickel content of at most 15 atomic %, preferably at most 10 atomic %, based on the total metal atomic content of the composition (iii); or more than one of these.
39. The method according to any one of claims 19 to 38, wherein at least one of compositions (i), (ii) or (iii) additionally comprises at least one iridium compound in an amount which provides a total iridium content of at most 15 atomic %, preferably at most 10 atomic %, based on the total metal atomic content of the composition.
40. A method according to any one of claims 19 to 39, wherein the electrically conductive solid substrate consists essentially of a valve metal, preferably titanium.
41. An electrolytic chlorine production system comprising the electrolytic anode structure according to any one of claims 1 to 18 or the electrolytic anode structure obtainable by the method according to any one of claims 19 to 40.
42. An electrolytic process for the evolution of chlorine gas from an aqueous solution containing chloride ions, comprising passing an electric current through the solution in an electrolytic cell comprising an electrolytic anode structure according to any one of claims 1 to 18 or an electrolytic anode structure obtainable by a process according to any one of claims 19 to 40, wherein chlorine gas is evolved from the aqueous solution at the anode.
43. The electrolysis process of claim 42, wherein the evolution of chlorine from the aqueous solution is promoted by the catalytic action of the composite metallurgical layer covering the surface of the anode.
44. An electrolysis process according to claim 42 or 43, wherein the chlorine gas evolved by the process is used as a biocide to disinfect water.
45. The electrolysis process of claim 44, wherein the chlorine is used to disinfect ballast water, or industrial or municipal wastewater.
46. An electrolytic process according to claim 42 or 43, wherein the process is a chlor-alkali process for the generation and recovery of chlorine gas.
